Data Communication Subsystem Reliability Optimization Scheme of Upgraded Shanghai Rail Transit Line 3 and Line 4 - WANG Xin (Chengshi guidao jiaotong yanjiu)
Objective During the evolution of existing DCS (data communication subsystem) towards a dual-mode four-network system in the major signaling system renovation project of Shanghai Rail Transit Line 3 and Line 4, there is a hidden risk that the trackside DCS single-point fault may cause the failure of individual vehicle-wayside communication network. It is needed to optimize DCS reliability through adjusting the communication network structure. Method Based on TACS (train autonomous circumambulate system) structure and operation context, the DCS network structure is analyzed to identify key nodes and links affecting DCS reliability. The optimization scheme for DCS reliability is elaborated from both device and protocol layers. Field tests of operating trains on a sample section in the optimized scheme are conducted to evaluate the reliability of DCS. Result & Conclusion The optimized DCS demonstrates high reliability, it significantly enhances the overall performance of signaling system.